Words or Word Forms in the Particle Role: The Case of Slovene - Žele, Andreja (Slavistica Vilnensis, 2023)
This paper presents particles and other words used as particles in Slovene. It is particularly focused on the conversion of other parts of speech into particles. The functional structuralist approach is adopted, which classifies parts of speech in terms of their syntactic-semantic role in the clause. The particle as a dynamic function word as well as a clause modifier is presented from both a theoretical and practical standpoint and thus the paper concerns both linguistic observations on particles and the practical, i.e. lexicographic, treatment of particles in Slovene texts. With true particles, the text often alternates between a stressed modal role expressing the speaker’s evaluation of what is being commu- nicated, and a related connective role. Various situational contexts in communication cause syntactic-semantic inversions between the ex- pressive and connective roles to be very common and ordinary, thereby functionally likening particles to conjunctions. A particle as a nonmember of sentence has neither substantive nor grammatical in- dependent meaning and is therefore often in a conversion relationship with other parts of speech. In Slovene, it is thus confirmed that at least 25% of all particles especially due to their nonindependent generalized meaning, can be in a conversion relationship with other parts of speech. More frequent conversion relationships include interjection → particle, adverb → particle, conjunction → particle, noun → particle, verb → particle.